Bipartite function of a small RNA hairpin in transcription antitermination in bacteriophage lambda. - Chattopadhyay, S (1995)
Transcription of downstream genes in the early operons of phage lambda requires a promoter-proximal element known as nut. This site acts in cis in the form of RNA to assemble a transcription antitermination complex which is composed of lambda N protein and at least four host factors. The nut-site RNA contains a small stem-loop structure called boxB. Here, we show that boxB RNA binds to N protein with high affinity and specificity. While N binding is confined to the 5' subdomain of the stem-loop, specific N recognition relies on both an intact stem-loop structure and two critical nucleotides in the pentamer loop. Substitutions of these nucleotides affect both N binding and antitermination. Remarkably, substitutions of other loop nucleotides also diminish antitermination in vivo, yet they have no detectable effect on N binding in vitro. These 3' loop mutants fail to support antitermination in a minimal system with RNA polymerase (RNAP), N, and the host factor NusA. Furthermore, the ability of NusA to stimulate the formation of the RNAP-boxB-N complex is diminished with these mutants. Hence, we suggest that boxB RNA performs two critical functions in antitermination. First, boxB binds to N and secures it near RNAP to enhance their interaction, presumably by increasing the local concentration of N. Second, boxB cooperates with NusA, most likely to bring N and RNAP in close contact and transform RNAP to the termination-resistant state.